2020
DOI: 10.3390/agronomy10071030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt-Tolerant Bacterial Inoculations on Rice Seedlings Differing in Salt-Tolerance under Saline Soil Conditions

Abstract: Salt-tolerant plant growth-promoting rhizobacteria (PGPR) could be an alternative to alleviate salinity problems in rice plants grown in the coastal areas. This study was conducted to isolate and characterize salt-tolerant PGPR and observe their effects on the physiological and biochemical properties of rice plants grown under non-saline and saline glasshouse conditions. Three strains were selected based on their salt-tolerance and plant growth-promoting properties under in vitro saline conditions. These strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 55 publications
6
28
0
Order By: Relevance
“…Arora et al (2010) reported that, under salinity stress, bacteria can bind Na ions through the secretion of EPS, which reduces Na toxicity in soil. A higher population of EPS-producing bacteria in the root rhizosphere reduces the concentration of Na availability for uptake and alleviates the NaCl effect on plants (Shultana et al, 2020b). In current observations, a decrease in Na content in bacterial-inoculated rice plants might be due to their EPS-producing activity (Supplementary Figure 1B).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Arora et al (2010) reported that, under salinity stress, bacteria can bind Na ions through the secretion of EPS, which reduces Na toxicity in soil. A higher population of EPS-producing bacteria in the root rhizosphere reduces the concentration of Na availability for uptake and alleviates the NaCl effect on plants (Shultana et al, 2020b). In current observations, a decrease in Na content in bacterial-inoculated rice plants might be due to their EPS-producing activity (Supplementary Figure 1B).…”
Section: Discussionsupporting
confidence: 46%
“…Amacher et al (2000) revealed that PGPB reduces salinity stress in maize and wheat by ∼50%. Similarly, leaf chlorophyll concentration is an indicator of salt tolerance and responds to increasing salinity stress (Habib et al, 2016;Shultana et al, 2020b). Salinity stress increases chlorophyllase activity, decreases chlorophyll synthesis, and destroys pigment proteins, decreasing chlorophyll pigment in alfalfa, lettuce, wheat, okra, and basil (Han and Lee, 2005;Bashan et al, 2006;Heidari and Golpayegani, 2012;Habib et al, 2016;Ansari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, inoculation of salt-tolerant PGPB, namely, Bacillus tequilensis strain UPMRB9 and Bacillus aryabhattai strain UPMRE6 on rice plants were shown to have beneficial effects on photosynthesis, transpiration, and stomatal conductance [ 114 ]. Shultana et al demonstrated that the inoculation of B. tequilensis strain UPMRB9 on the MR297 rice variety improved total chlorophyll content by 28% and reduced electrolyte leakage by 92% [ 115 ]. Increments of relative water content and reduction in the Na/K ratio were also found upon inoculation of B. tequilensis strain UPMRB9 and B. aryabhattai strain UPMRE6 on rice plants.…”
Section: The Pgpb As Biocontrol Agentmentioning
confidence: 99%
“…Other studies have reported that the inoculation of PGPB (P. fluorescens biotype F, P. fluorescens CECT 378T, B. tequilensis, B. aryabhattai, Providencia stuartii, Pantoea agglomerans, or Arthrobacter sp.) in plant rhizosphere under salinity stress resulted in an increased K + /Na + ratio [4,76,128,129]. All PGPB presented various PGP traits, the combined action of which leads to the amelioration of salinity stress to plants.…”
Section: Plant Ion Homeostasismentioning
confidence: 99%